Water exchange mechanisms between Ria de Aveiro and the Atlantic Ocean - Silva, P. A.
The water exchange between the ocean costal waters and the Ria de Aveiro coastal lagoon has an important role in the environmental aspects inside the lagoon. A well-tested 3D coastal circulation model is applied to establish different scenarios of this interaction. The numerical experiments, employing lagrangian techniques, were devised to study the effect of the tide and wind driven flows on the patterns of the residual circulation in the neighborhoods of the entrance of the coastal lagoon, and to delimitate the ocean domain of influence of the Ria de Aveiro, where this exchange is important.